The Liquidity Management and Profitability of Joint Venture Banks in Nepal - Pant, Chet Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The main objective of this study is to establish a connection between liquidity management and the effect of profitability of joint venture banks in Nepal. We observed the data from Nepal's top five joint venture banks over ten years, from 2012 to 2021. We used financial statements to collect information. In our analysis, we used different indicators like the current ratio (CR), loan-to-total deposit (LTD), capital-to-asset ratio (CAR), and non-performing loans (NPL) as measures of liquidity. We treated these as independent variables and Return on assets (ROA) as dependent variable. Our findings show the positive link between ROA and CR, meaning higher CR is connected to greater ROA. However, the study reveals an unfavorable relationship between NPL and ROA, suggesting higher NPL leads to lower ROA. As a result, our research advises banks to keep liquidity only as long as necessary for specific liabilities, avoiding unnecessary holding of liquidity, which could reduce profitability.